Artificial Reality: Exploring the Potential Threats of Artificial Intelligence - Fernández Mateo, Joaquín (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The purpose of this paper is to explore the technological and computational innovations that have led to the growing concern about the existential risks of artificial intelligence. To do so, it is proposed to review the unavoidable events of the history of modern science and computing, in order to land on the current generative artificial intelligences. Given the increasing realistic approximation of images generated by artificial intelligence, it is conjectured that they will soon be confused with photographic images.